Konsep Pemikiran Pendidikan Imam Ibnu Jamaah - Permatasari, Indah Gilang; Rasyid, Faiz; Linggawijaya, Hamzah; Mulyanto, Mulyanto (Lembaga Yasin AlSys, 2026)
Modern education today faces serious challenges in the form of a character crisis and moral degradation amid the wave of digitalization, while the exploration of classical thinkers’ ideas as a foundation for strengthening character education has not been optimally utilized. This study aims to explore in depth the concept of Islamic education thought according to Imam Ibnu Jama’ah (1241–1333 AD) and to analyze its relevance to twenty-first-century educational problems. The research method used is qualitative with a studi pustaka (library research) approach, focusing on the monumental work Tadzkirat al-Sāmi’ wa al-Mutakallim fī Adab al-‘Ālim wa al-Muta‘allim. The results show that Ibnu Jama’ah’s concept of education emphasizes the integration between transfer of knowledge and transfer of value, with several main elements, namely: (1) the teacher as a moral role model; (2) students who prioritize purification of the soul; (3) a curriculum that integrates spiritual values; and (4) learning methods that balance the power of memorization with intellectual creativity. The relevance of Ibnu Jama’ah’s thought to twenty-first-century education lies in the strengthening of character education, in which adab (ethics) is positioned as the main foundation before the mastery of knowledge, so that it is expected that a generation will emerge that is not only intellectually intelligent but also morally excellent.